2017
DOI: 10.1063/1.5003223
|View full text |Cite
|
Sign up to set email alerts
|

Bi-stability of micro-plates: A sensitive mechanism for differential pressure measurements

Abstract: The electrostatic instability (pull-in) of a flat electrode in a parallel plate capacitor has been shown to be highly sensitive to external mechanical loads such as pressure. In this paper, we substantiate the possibility of prompting additional unstable configurations in such a system, with a remarkable sensitivity to the applied pressure. This additional instability has significant advantageous properties for sensing purposes. In addition to the high sensitivity and robustness of the pull-in voltage measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Therefore, the system becomes bi-stable, and sweeping the DC voltage over these limit points leads to a snap-through behavior between coexisting solution branches or failure of the system. This bi-stability can be of interest for actuation or binary sensing mechanisms (for differential pressure measurements for example [15]). …”
Section: Sweep Over DC Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the system becomes bi-stable, and sweeping the DC voltage over these limit points leads to a snap-through behavior between coexisting solution branches or failure of the system. This bi-stability can be of interest for actuation or binary sensing mechanisms (for differential pressure measurements for example [15]). …”
Section: Sweep Over DC Voltagementioning
confidence: 99%
“…It has been shown that the critical voltage and deflection of the flexible electrode depend on the material properties, geometry and dimensions of the flexible electrode, and the initial gap size between the two electrodes. Particularly, for circular plate-like electrodes, the critical deflection in static pull-in varies between 51 and 71% of the initial gap between the electrodes, depending only on the thickness of the structure [14,15].…”
mentioning
confidence: 99%
“…Bi-stability in an electrostatically actuated microplate can be obtained mainly by two ways. In the first way, the plate has initial natural arc shape in one direction and electrostatic or mechanical or other actuation force is applied to the opposite direction [24,25], and the second way is to generate this arc shape in the flat plate by applying transverse pressure and then actuation force is applied to the opposite direction [26,27]. In both the cases, there is a threshold limit of initial curvature or transverse pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They produced an approximate solution to study the effects of both electrostatic force and external pressure on the natural frequency of clamped circular microplate with the help of the energy equivalent method. Moreover, the effect of transverse pressure and in-plane load on static characteristics of MEMS plates were also investigated by many researchers [17,18]. On the other hand, in the field of NEMS devices, Chen et al [19] examined the frequency response of monolayer graphene resonator for various nanoelectromechanical applications.…”
Section: Introductionmentioning
confidence: 99%